THE ROLE OF THE TEACHER IN DEVELOPING STUDENTS' LEARNING CREATIVITY IN CIVIC EDUCATION LEARNING AT GMIT KUANINO I ELEMENTARY SCHOOL - Rosita Liunesi; Heryon B. Mbuik; Cornelia A. Naitili; Yulsy M. Nitte (Journal of Innovative Technologies in Learning and Education, 2025)
The teacher’s role in reminding students of their learning creativity is one of the integral activities that must be included in learning activities. Apart from providing and transferring knowledge, teacher’s are also tasked with increasing children’s creativity in learning. The learning process will be successful if student’s have motivation and creativity in learning. The aim of this research is to find out the role of teachers in developing student learning creativity. This research uses qualitative research, using a descriptive approach, because this research is used to describe and analyse teacher’s efforts to increase student learning motivation in PKN learning to imprive srudent learning achievement at GMIT Kuanino 1 elementary school. The teacher’s efforts to develop student’s learning creativity in class IV citizenship education at SD GMIT Kuanino 1 is to obtain additional learning resources usung the internet. This is done so that student’s and learn develop their creativity well in participating in citizenship education lessons.